Large strain and low hysteresis in (1-x)Bi0.5(Na0.75K0.25)0.5TiO3-xSrTiO3 lead-free piezoceramics. (12th May 2021) - Liu, Zixuan; Ruan, Tingting; Li, Qiong; Liu, Yunfei; Lyu, Yinong; Mao, Minmin
Abstract: (1- x )Bi0.5 (Na0.75 K0.25 )0.5 TiO3 - x SrTiO3 (BNKT- x ST) incipient piezoelectric ceramics with x = 0.05-0.35 were fabricated using solid-state reaction technique. The microstructure and electrical properties are discussed as functions of ST content. The X-ray diffraction patterns confirm that all the compositions form a solid solution without any secondary phase. As the ST content increases, the grain growth is inhibited, and the ferroelectric phase transforms into the relaxor phase, which can be confirmed by the P-E and I-E loops. For the compositions of x = 0.05, 0.30 and 0.35, a large strain of 0.28%, 0.24% and 0.18% with a low hysteresis of 16.2%, 10.0% and 4.7% can be obtained. We propose that the large strain and low hysteresis behavior are beneficial from the disruption of long-range ferroelectric phase and the increase in relaxor phase, which should provide a feasible paradigm to promote the applications of precise micro-actuators.